Management of empyema in children: a clinical audit. (24th May 2012) - Irving, K; Snowden, C; Blackburn, S; Alexander, E; Hallows, R; Chetty, K; Seddon, P
Abstract : Aim: National guidelines for the management of paediatric pleural infections (empyema) were introduced by the British Thoracic Society in 2005, and our institution implemented a trust guideline in 2008. We reviewed the management of empyema in our children's hospital in accordance with both guidelines. Methods: Cases of empyema admitted April 2005-March 2011 were identified through clinical coding, surgical, radiological and microbiological databases. Management and clinical course were extracted onto a proforma, following an initial pilot. Findings were presented at the paediatric clinical governance meeting. Results: 101 children, median age 5.3 (range 0.6 to 16.3) years, were admitted for median 8 (range 2 to 28) days. 23 children (23%), with ultrasound median effusion depth 1.6 cm, were managed conservatively with IV antibiotics alone. Initial surgical management (77%) included 51% closed chest drainage, 23% video-assisted thoracoscopic surgery (VATS) and 3% open thoracotomy. Intrapleural urokinase was used in 89% of the 78 patients surgically managed: 87% with closed chest drain, 70% of VATS and 67% of open thoracotomy procedures. A quarter (24%) of all chest drains dislodged accidentally at a median 3 (range 1 to 6) days after surgery. 13% of those surgically managed required a second procedure. 92 (91%) patients did not have an anti-streptolysin O-titre (ASOT), nor 27 (27%) a blood culture sent. Pleural fluid was sent for culture in 76 (97%) of surgically managed patients, 13 (16%) of these having differential count/cell cytology. There was limited use of pneumococcal PCR in culture negative patients. Initial IV antibiotic use was with Co-Amoxiclav (46%) or Cephalosporins (52%), either alone or in combination with other antibiotics. Total duration antibiotic therapy was median 21 (range 7-40) days, with variation in intravenous and oral course length. Conclusion: The majority of children were managed according to guidelines. Almost a quarter were managed conservatively. Urokinase use was varied, with shortened courses, and a number of cases of VATS or thoracotomy receiving urokinase. The high rate of drain dislodgement is of concern, and will be addressed by the introduction of pig tail catheters. Trust guidance regarding appropriate investigations have been modified.